Developing Human Resource for Meeting Pulses Demand - Purushottam,; Singh, Baldeo (Indian Journal of Extension Education, 2011)
The pulses production has remained around 13-15 million tonnes while annual domestic demand has risen to 18-19 million tonnes. The projected pulse requirement by the year 2030 is estimated at about 32 million tonnes. Adoption of technological innovations in pulses and their importance in soil sustainability needs human resource development in the country. The human resource associated in pulses development is not enough competent in meeting the pulses demand causing heavy import of pulses in India. The vast populations of pulses growers can be excelled through systematic training and development approaches. The human resource in pulses development can be grouped broadly into pulse growers of marginal, small, and big farmers; change agents, subject matter specialist and master trainers.  The curriculum on pulses trainings are not in need of present day filed situation therefore ineffective to these category of people. In the present scenario of communication technologies, the past approaches of training and development would not be appropriate and effective. Therefore, specific training and development modules are required for pulses growers, women farmers, trainers, rural entrepreneurs and input dealers. These modules will be effective to enhance knowledge and skills of pulses growers in the country. The paper deals with trainees, training curricula contents, training methods, trainers, farmers motives in pulses cultivation, multi media training approach, effective training plan and training modules in pulses development.